Incidence, pathology and diagnosis of fowlpox, pigeonpox and duckpox in Asom - PATHAK, N; BARUAH, G K; PATHAK, D C; UPADHYAYA, T N; BARMAN, N N; KALITA, N; DEKA, P (The Indian Journal of Animal Sciences, 2017)
A study was conducted to see the incidence of avian pox in different districts of Asom and one district of Nagaland, where outbreaks, 29 of fowlpox, 13 of pigeonpox and 3 of duckpox were recorded. The age wise morbidity and cause specific mortality in case of fowlpox was recorded at 0–8 weeks (19.63 and 23.60%), at 9–20 weeks (5.57 and 14.43%) and above 20 weeks (1.39 and 11.11%), respectively. Likewise, in pigeonpox, morbidity and cause specific mortality were recorded at 0–8 weeks (11.11, 0%), 9–20 weeks (30.68, 37.03%) and above 20 weeks (35.08, 30%), respectively. Again in case of duckpox, morbidity was recorded at 0–8 weeks (10%), 9–20 weeks (0%) and above 20 weeks (6.66%), while no mortality was recorded among the ducks. External examination revealed erosions, crusts and several small, multifocal to coalescing wart-like nodules on various parts of the affected birds. During post-mortem examination, few birds showed fibronecrotic lesions on mucous membrane of the oral cavity and upper respiratory tract. Histopathological examination of the scab samples revealed intracytoplasmic eosinophilic inclusion bodies. During ultrastructural study, inclusion bodies were seen in the cytoplasm of the skin epithelium,which consist of numerous, dumbbell-shaped bodies typical of pox virions. During molecular diagnosis, out of 29fowlpox, 9 pigeonpox and 3 duckpox suspected samples 86.20, 77.77 and 100% samples, respectively, were foundpositive by polymerase chain reaction.